Apakah Sistem Pengendalian Intern Penjualan dan Penerimaan Kas Menjamin Keamanan Harta Perusahaan ? (Studi Kasus pada PT. Pacific Lubritama Indonesia (PLI) di Bandar Lampung) - Syamsu Rizal; Ade Kurniawan; Goenawan GOENAWAN (Universitas Bandar Lampung (UBL), 2011)
This study aimed to evaluate whether internal control is applied to the company was able to secure the company's assets. While the usefulness of this research is as an input for the interested parties, so that is a benchmark in determining further steps in particular with regard to the provision of credit and internal control. Authors proposed hypothesis is that the internal control system implemented by PT. Pacific Lubritama Indonesia has not been able to secure company assets.The analysis showed that the company has implemented the division of tasks and responsibilities between workers with one another can each control, allow the small diversion and fraud. So is the fault of consumer credit, particularly with respect to financial problems or income can be reduced as small as possible. Analysis shows that the system of internal control of credit to the company have not been adequate so that the hypothesis that the internal control system implemented by PT. Pacific Lubritama Indonesia has not been able to secure property and the company is completely acceptable.